2012
DOI: 10.1021/es2039882
|View full text |Cite
|
Sign up to set email alerts
|

Thresholds for the Effects of Pesticides on Invertebrate Communities and Leaf Breakdown in Stream Ecosystems

Abstract: We compiled data from eight field studies conducted between 1998 and 2010 in Europe, Siberia, and Australia to derive thresholds for the effects of pesticides on macroinvertebrate communities and the ecosystem function leaf breakdown. Dose-response models for the relationship of pesticide toxicity with the abundance of sensitive macroinvertebrate taxa showed significant differences to reference sites at 1/1000 to 1/10,000 of the median acute effect concentration (EC50) for Daphnia magna, depending on the model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
165
4
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 225 publications
(197 citation statements)
references
References 62 publications
15
165
4
4
Order By: Relevance
“…In South Africa, Dabrowski et al (2001) identified pesticide effects on a stream. A recent meta-study of Schäfer et al (2012) identified pesticide effects in eight data sets comprising exposure data and effect data.…”
Section: Uncertainties In Extrapolating To Real Field Situationsmentioning
confidence: 99%
“…In South Africa, Dabrowski et al (2001) identified pesticide effects on a stream. A recent meta-study of Schäfer et al (2012) identified pesticide effects in eight data sets comprising exposure data and effect data.…”
Section: Uncertainties In Extrapolating To Real Field Situationsmentioning
confidence: 99%
“…an increase in the number of mixture components has been suggested to lead to a decrease in the range of deviation from toxic additivity (the Funnel hypothesis) (Warne and Hawker, 1995). For log max TU D.magna the suggested threshold for effects of pesticides in the field is at least -3 (Schäfer et al, 2012b).…”
Section: Data Treatmentmentioning
confidence: 99%
“…The only exceptions are two studies that addressed effects of salinity (8,9). Hence, although chemical contaminants are well known as an important driver for biodiversity loss (1,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), there is scarce empirical evidence to support such opinion for the large-scale taxonomic pools.…”
mentioning
confidence: 99%
“…Essentially, it remains unknown whether, to what degree, and at what concentrations pesticides cause the species losses at the regional scale. However, there are many investigations showing the effects on the local biodiversityrelated parameters in both freshwater (16)(17)(18)(19)(20)(21)(22)(23) and terrestrial systems (14,15,(24)(25)(26)(27). Thus, the previous studies with freshwater invertebrates reliably measured the aquatic pesticide concentrations and identified local (site-scale) changes in the abundance of the taxa specifically vulnerable to pesticides and structural community alterations, e.g., using the species-at-risk (SPEAR) pesticides indicator (16)(17)(18)(19)(20)(21), or the abundance of separate species (22) (for different taxonomic groups, see ref.…”
mentioning
confidence: 99%